Transcriptional activation by Sp1 as directed through TATA or initiator: specific requirement for mammalian transcription factor IID. - Smale, S T (1990)
Transcription of mammalian genes by RNA polymerase II often begins at a specific nucleotide, whose location is determined either by an upstream DNA element known as a TATA box or by an element positioned at the transcription start site called an initiator (Inr). By in vitro analysis of synthetic promoters, we demonstrate here that the TATA and Inr elements are functionally similar and that the Inr is contained between nucleotides -3 and +5 relative to the initiation site. Moreover, we found that a mammalian transcription factor IID (TFIID) protein fraction is required for transcriptional stimulation by an Sp1-dependent activating element placed upstream of either TATA or Inr elements. However, in these assays, the yeast TATA-binding protein, which previously was shown to function similarly to mammalian TFIID, could not efficiently substitute for the mammalian TFIID fraction. These results demonstrate that mammalian TFIID is functionally distinct from the yeast TATA-binding protein and may contain additional subunits or domains that are important for transcriptional activation from some promoters.